Expression of internal reproductive barriers in a germplasm bank accession of the wild potato Solanum chacoense Bitter in three ex situ regeneration cycles - Poulsen Hornum, Anabela; Camadro, Elsa Lucila (Springer Nature, 2021)
Wild potatoes (Solanum sp.) are important reservoirs of desirable genes for potato breeding. Most of them are diploid and obligate outcrossers, with both sexual and asexual reproduction. Samples of natural populations are ex situ conserved as accessions in germplasm banks for basic and applied ends, and are regenerated when seed number, seed viability or both decrease. The possible action of within accession internal reproductive barriers is not considered in the current seed regeneration protocols, in which 20 to 25 plants are cultivated for the crossing work. Notwithstanding, the effective number of progenitors (Ne) in every seed regeneration cycle might be reduced in relation to the real number (N) of plants if internal reproductive barriers were acting; this process can eventually lead to gene erosion. To ascertain if Ne = N in seed regeneration of one randomly provided accession of S. chacoense Bitter, pollen viability and size, plus pollen-pistil relationships and number and type (according to endosperm development) of seeds/fruit were studied, respectively, at the individual plant and genotypic combination levels. Two types of barriers, pre-zygotic (pollen-pistil self- and cross-incompatibility) and post-zygotic (male sterility and inviability and weakness of F1 hybrids) were detected in three growing seasons, indicating that not all genotypes in this accession made an equal allele contribution to the next generation. These results should be an alert for germplasm bank curators of wild potatoes and other crop wild relatives. Since the objective of germplasm banks is the ex situ maintenance of the natural genetic diversity, strategies need to be devised based on genetic premises.